The ICT competencies of new accounting students of different intake channels: The case of the Universiti Utara Malaysia - Harun Rasit, Mohd Hadzrami; Rosli, Khairina; Ibrahim, Mohammad Azhar (Malaysian Educational Technology Association, 2012)
This study aims to investigate the level of information and communication technology (ICT) competency possesses by new accounting students at the Universiti Utara Malaysia according to their intake channels.The study examines five software applications deemed critical for an accountant, namely, word processing; spreadsheet; database; PowerPoint presentation; and Internet and email.A survey was conducted on 182 first year accounting students. Overall, students from the diploma intake channel are found to possess the ICT competency better than those from other intake channels. The competency of students from Matriculation and STPM intake channels in spreadsheet is found to be below average.All students regardless of their intake channels were found to be less competent in database application.